Vaksin Dengue - Sutaryo Sumadiono, Syarifah Hanum P (Berita Kedokteran Masyarakat (BKM), 2003)
Dengue hemorrhagic fever remains one of the world's most important cause of morbidity and mortality. Vector control has been proven to be an inadequate preventive measure that a new strategy is needed to alleviate the increasing burden of illness of this disease. Vaccination against dengue has become a promising solution to this problem. Base on antibody dependent pathogenesis, the ideal vaccine should be prevent all of four serotypes, cheap, effective, minimal side effect, genetic and antigenetic stable, and long life protection. There are several types of vaccines currently under investigation, among them are vaccines made by classic attenuation method, attenuation by way of genetical engineering, sub unit vaccines of purified protein and protein made by gen cloning techniques, vaccine using vaccinia virus as vector and DNA vaccine. The development of biomolecular engineering is expected to enable the production of vaccine in large quantity which is economically cheaper. Until recently vaccine produced by attenuation and recombinant are availeble for production, while other vaccine candidates are still under investigation. Keywords: dengue, vaccine, recombinant